2017
DOI: 10.1002/chem.201604802
|View full text |Cite
|
Sign up to set email alerts
|

Borinic Acid Catalysed Reduction of Tertiary Amides with Hydrosilanes: A Mild and Chemoselective Synthesis of Amines

Abstract: A reduction of various aryl, alkyl, and α,β-unsaturated amides with phenylsilane, catalysed by a borinic acid, is reported. The unprecedented reaction was carried out under very mild conditions and led to useful amines. Furthermore, the reaction tolerates a variety of functional groups. Initial investigations implicated that an intermediate diarylhydroborane is involved in the reaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Since this important discovery, boron‐based catalysts were used as Si–H bond activators in many chemical transformations . Our group recently developed 2‐chlorophenylborinic acid 1a for the challenging catalysis of amide and phosphine oxide reductions . Noticeable, lower temperature was used and high chemoselectivity was achieved when compared to B(C 6 F 5 ) 3 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Since this important discovery, boron‐based catalysts were used as Si–H bond activators in many chemical transformations . Our group recently developed 2‐chlorophenylborinic acid 1a for the challenging catalysis of amide and phosphine oxide reductions . Noticeable, lower temperature was used and high chemoselectivity was achieved when compared to B(C 6 F 5 ) 3 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy of mention that in the absence of photochemical activation, the reduction of simple tertiary amides at room temperature by use of a3 dt ransition-metal catalyst is, to the best of our knowledge,unknown. [21] In this context, we subsequently examined the ability of 1 to effect such unprecedented transformations (2 mol % 1,2 5 8 8C, 18 h; Figure 2). We were pleased to observe that for several of the tertiary amide substrates under investigation herein, high conversion into the desired tertiary amine was achieved under room-temperature conditions,i ncluding the formation of Nbenzylpiperidine (2a), N-benzylmorpholine (2f), tribenzylamine (2h), and N,N-dimethylbenzylamine (2l).…”
mentioning
confidence: 99%
“…Interestingly, it was observed that 1 a in the presence of excess PhMe 2 SiH was slowly converted to (C 6 F 5 ) 2 BH 2 (Piers’ borane), with the corresponding 19 F NMR signals at δ −131.6, −149.0, and −160.5 ppm in CDCl 3 . The transformation of 1 into 2 was highly accelerated by employing more reactive silanes, such as PhSiH 3 (20 equiv) or TMDS (200 equiv), resulting in quantitative formation of 2 within 10 min at 25 °C (see the Supporting Information) …”
Section: Methodsmentioning
confidence: 99%